HISTORIS, KEMAJUAN DAN PENDIDIKAN DINASTI ABBASIYAH - Shofil Fikri; Helliyatul Arifina Mahbubi (Tarbawi, 2021)
The Abbasid Daulah or what we know as the Bani Abbasids was the third Islamic caliphate after the Umayyahds, the Abbasids ruled between 750-1258 AD, apart from being the longest caliphate in Islam, namely five centuries. The Abbasids also succeeded in making Islam the center of world knowledge. During this period, Islam achieved glory in various fields, including science. Progress in this field began with translating foreign manuscripts or books, especially Greek, into Arabic. The founding of the Abbasid Daula was motivated by chaos within the Umayyad Daula caused by the caliphs, including: Abdullah Al-Saffah ibn Muhammad ibn Ali ibn Abdullah ibn Al-Abbas, Abu Ja’far with the title Al-Mansur. Al-Qubbah Al-Khadhra’, Al-Saffah was the first caliphthe Abbasids, whose descendants were Abdullah ibn Al-Abbas, who was a friend of the prophet, were also transmitters of hadith.